Inhibiting the NLRP3 Inflammasome With Methylene Blue as Treatment Adjunct in Myelodysplasia - Kast, Richard E. (Frontiers in Oncology, 2018)
Myelodysplasia refers to a group of clonal hematopoietic neoplasms characterized by genetic heterogeneity, different clinical behaviors and prognoses. Some of this group of bone marrow failure conditions have known external causes, some are of unknown origin. Within marrow, intracellular and extracellular elements of the innate immune system are activated and contribute to creation of multiple cytogenetic abnormalities and are central to the mode of hematopoietic cell failure. Basiorka, Sallman, et al showed that NLRP3 inflammasome activity is essential to the innate immune system’s destruction of marrow hematopoietic cells commonly in myelodysplasia. In April 2018 Hao et al reported that methylene blue inhibits rat NLRP3 inflammasome function. Methylene blue has been in continuous use in humans for over a century. It is associated with an eminently benign side effect profile in human use. If as in rodents, methylene blue also inhibits NLRP3 inflammasome function in human myelodysplasia a trial of adjunctive methylene blue treatment in transfusion dependent, low risk myelodysplasia where marrow inflammation and apoptosis predominates, would be worth trying.